Nutrient management of guinea grass (Panicum maximum J.) under open and shaded conditions - Lekshmi P (Department of Agronomy, College of Agriculture, 2004)
A field experiment was conducted at the Instructional Farm, College of Agriculture, Vellayani, Thiruvananthapuram, Kerala state to find out the nitrogen and phosphorus requirement for guinea grass (Panicum maximum J.) under zero and 50 per cent shade levels. The influence of shade levels, nitrogen and phosphorus application on growth parameters, fodder yield, quality of produce, physiological parameters, uptake of nutrients, chemical properties of soil and economics was investigated. Two levels of shade (0 and 50 per cent), three levels of nitrogen (100, 200 and 300 kg ha") and three levels of phosphorus (25, 50 and 75 kg ha") were combined to form eighteen treatment combinations. The experiment was laid out in split plot design with three replications. Results of the experiment revealed that lower levels of shade as well as higher- levels of nitrogen and phosphorus had significant positive influence on improving the fodder production potential of guinea grass. The lower levels of shade and higher doses of nitrogen and phosphorus were found to increase significantly the growth parameters namely number of tillers and leaf: stem ratio and physiological parameters like leaf area index, CGR, RGR and NAR. , Lower levels of shade and higher doses of nitrogen and phosphorus registered maximum green fodder yield in all the five harvests. Total green fodder yield was also highest at open and at higher levels of nitrogen and phosphorus. Similar results were obtained in the case of dry fodder yield also. Quality parameters of the forage significantly improved as shade progresses. Higher levels of nitrogen and phosphorus registered higher crude protein and chlorophyll contents and lower crude fibre content.